Modification of polymethylmethacrylate bone cement with halloysite clay nanotubes - Tamer M. Hamdy (BMC Oral Health, 2024)
Abstract Background Polymethylmethacrylate (PMMA) bone cement is used in orthopedics and dentistry to get primary fixation to bone but doesn’t provide a mechanically and biologically stable bone interface. Therefore, there was a great demand to improve the properties of the PMMA bone cement to reduce its clinical usage limitations and enhance its success rate. Recent studies demonstrated that the addition of halloysite nanotubes (HNTs) to a polymeric-based material can improve its mechanical and thermal characteristics. Objectives The purpose of the study is to assess the compressive strength, flexural strength, maximum temperature, and setting time of traditional PMMA bone cements that have been manually blended with 7 wt% HNT fillers. Methods PMMA powder and monomer liquid were combined to create the control group, the reinforced group was made by mixing the PMMA powder with 7 wt% HNT fillers before liquid mixing. Chemical characterization of the HNT fillers was employed by X-ray fluorescence (XRF). The morphological examination of the cements was done using a scanning electron microscope (SEM). Analytical measurements were made for the compressive strength, flexural strength, maximum temperature, and setting time. Utilizing independent sample t-tests, the data was statistically assessed to compare mean values (p < 0.05). Results The findings demonstrated that the novel reinforced PMMA-based bone cement with 7 wt% HNT fillers showed higher mean compressive strength values (93 MPa) and higher flexural strength (72 MPa). and lower maximum temperature values (34.8 °C) than the conventional PMMA bone cement control group, which was (76 MPa), (51 MPa), and (40 °C), respectively (P < 0.05). While there was no significant difference in the setting time between the control and the modified groups. Conclusion The novel PMMA-based bone cement with the addition of 7 wt% HNTs can effectively be used in orthopedic and dental applications, as they have the potential to enhance the compressive and flexural strength and reduce the maximum temperatures.